The misadventures of Winnie the Witch - Owen, Laura; Paul, Korky (Oxford Oxford University Press, 2018)
Winnie is full of mad-cap schemes and plans to put her magic to good use. Wilbur is her long-suffering best friend, and everyone's favourite moggy. From Winnie's knicker shop, where spiders sew up the lacy trims, to Winnie's creativity in the kitchen where she often cooks up such delicacies as turkey tonsil titbits, giggles are guaranteed!
Title taken from cover and spine. The title page still displays earlier title "The misadventures of Winnie the Witch".
"8 magical stories in colour" -- Cover.
First published as "The misadventures of Winnie the Witch" in 2011.
Keywords: Winnie,the Witch (Fictitious character) -- Juvenile fiction; Wilbur,(Fictitious character) -- Juvenile fiction; Witches -- Juvenile fiction